The Diagnostic and prognostic value of CXCL12 (SDF-1α) level in Mycobacterium tuberculosis infection and disease - Ilkay Koca Kalkan; Ayse Gozu; Ebru Tansel; Serife Nilgun Kalac; Belgin Samurkasoglu; Hulya Simsek (Journal of Infection in Developing Countries)
Introduction: New diagnostic tools are being investigated for rapid and accurate TB detection. We aimed to find out the diagnostic yield and accuracy of chemokine CXCL12 (SDF-1a) levels in diagnosing active TB (aTB) and making a differential diagnosis from other several infectious/non-infectious pulmonary conditions.